2000
DOI: 10.1034/j.1600-0412.2000.079011973.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐density vaginal Ureaplasma urealyticum colonization as a risk factor for chorioamnionitis and preterm delivery

Abstract: The degree of colonization with Ureaplasma urealyticum correlates strongly with an adverse effect on pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…infections, as well as genital infections, are linked to complicated pregnancy (PROM, chorioamnionitis, Caesarean delivery or funisitis) or neonatal outcome (low birth weight, gestational age < 37 weeks, neonatal sepsis, CLD, BPD) [23,24] but infants born premature by mothers with chorioamnionitis did not develop RDS despite the higher association of ureaplasma biovar 1 ( U. parvum ) colonisation with CLD [15]. As regards the clinical parameters of the pregnancy, apart from longer hospitalisation in newborns found positive for ureaplasma, compared with those negative with both methods (table 2), we did not find statistical differences between the two groups for small amount of our data, according to previous study [22].…”
Section: Discussionmentioning
confidence: 99%
“…infections, as well as genital infections, are linked to complicated pregnancy (PROM, chorioamnionitis, Caesarean delivery or funisitis) or neonatal outcome (low birth weight, gestational age < 37 weeks, neonatal sepsis, CLD, BPD) [23,24] but infants born premature by mothers with chorioamnionitis did not develop RDS despite the higher association of ureaplasma biovar 1 ( U. parvum ) colonisation with CLD [15]. As regards the clinical parameters of the pregnancy, apart from longer hospitalisation in newborns found positive for ureaplasma, compared with those negative with both methods (table 2), we did not find statistical differences between the two groups for small amount of our data, according to previous study [22].…”
Section: Discussionmentioning
confidence: 99%
“…in the female lower genital tract may be a risk factor for chorioamnionitis and adverse pregnancy outcomes, such as preterm birth (179)(180)(181)(182)(183)(184). A prospective study of 2,471 women attending an antenatal clinic demonstrated that Ureaplasma spp.…”
Section: Lower Genital Tract Ureaplasma Colonization Association Withmentioning
confidence: 99%
“…Abele-Horn et al 10,11 demonstrated a significantly higher incidence of chorioamnionitis in women colonized with Ureaplasma urealyticum. Yancey et al 12 reported similar results with group B streptococcal colonization.…”
mentioning
confidence: 99%